Clinical Assessment of Visual Motion Perception in Children With Brain Damage: A Comparison With Base Rates and Control Sample - van der Zee, Ymie J.; Stiers, Peter L. J.; Lagae, Lieven; Evenhuis, Heleen M. (Frontiers in Human Neuroscience, 2021)
Aim: In this study, we examined 1) the presence of abnormally low scores (below 10th percentile) in various visual motion perception aspects in children with brain damage, while controlling for their cognitive developmental delay; 2) whether the risk is increased in comparison with the observation and expectation in a healthy control group and healthy population Method: Performances of 46 children with indications of brain damage (Mage = 7y4m, SD = 2y4m) on three visual motion perception aspects (global motion, motion speed, motion-defined form) were evaluated. We used developmental age as entry of a preliminary reference table to classify the patient’s performances. Then we compared the percentages of weak performers with percentages expected in the healthy population using estimated base rates and the observed percentages in the control sample (n = 119) Results: When using developmental age as reference level, the percentage of weak performers on at least one of the three tasks was significantly higher than expected in the healthy population (19/46, 41% [95%CI: 28 - 56%], p = .03). In 15/19 (79% [95%CI: 61-97%] patients only one aspect of motion perception was affected. Four patients performed abnormally low on two out of three tasks, which is also higher than expected (4/46, 8.7%, 95%CI:2.4-20.8% vs 2.1%; z = 2.61, p <.01). The observed percentages in the patient group were also higher than found in the control group. Interpretation: There is some evidence that children with early brain damage have an increased risk of isolated and combined motion perception problems, independent of their performance IQ.